Testing pioneer positive deviance in Colombia - Vanegas, Carlos José (International Livestock Research Institute, 2024)
The International Livestock Research Institute (ILRI) has been testing the adaptation pioneers approach in the Program for Climate-Smart Livestock (PCSL) in African countries such as Kenya, Uganda and Ethiopia. Interventions in the field have identified a significant human resource pool in these countries with potential capabilities to boost the processes of replication and scaling up of good climate change adaptation practices to a broader level.